WATCHING SEQUEL MOVIE: THE ROLE OF CUSTOMER EXPERIENCE AND CUSTOMER SATISFACTION ON REPURCHASE INTENTION - Aprilia Dwi Arista; Yessy Artanti; Nindria Untarini; Monika Tiarawati (Jurnal Mebis, 2022)
WATCHING SEQUEL MOVIE: THE ROLE OF CUSTOMER EXPERIENCE AND CUSTOMER SATISFACTION ON REPURCHASE INTENTION